The Urgency of Eliminating the Norms "The Indonesia Army Are Prohibited From Doing Business" Through The Drafting of A Indonesia Army Law Based on A Human Rights Perspective - Gusman, Delfina (Ekasakti Journal of Law and Justice, 2024)
The constitution gives citizens freedom to engage in commercial activities not only to increase their economic income. But rather to encourage the quality of each individual to continue productivity. Currently, a variety of jobs have developed which can increase individual income, where the global economic cycle is better than in the past. Recently, there have been plans for every profession in the Indonesian National Army (TNI) to be able to do business. This plan is due to the Draft Law or what is called Bill Number 34 of 2002 concerning the TNI.  Polemic about eradicating norms"prohibition of the TNI in doing business” has become a matter of public concern at the moment, there are concerns that the TNI's role as a national defense soldier will be disrupted. This research is legal research (doctrinal research) with a legal approach (statues approach), analytical approach (analytical approach), and conceptual approaches (conceptual approach). The research results explain that First The National Army is not only to uphold, protect and safeguard the nation's sovereignty from Indonesian military and non-military attacks/threats, but can also participate in civil society activities such as helping victims of natural and non-natural disasters or joining the government as long as the orders of their superiors has been regulated in law.  Second, the rights to life of a TNI soldier are no different from civil rights, especially the rights to improve their daily welfare. Third, the urgency of eliminating the norm regarding "TNI is prohibited from doing business" is a legal effort to look at the situation progressively. Therefore, the abolition of the norm "TNI is prohibited from doing business" is a legal effort to protect their economic rights in improving the standard of living for those of their families.